A Study of the Financial Health and Growth Patterns of Infrastructure Finance Companies in India - Acharya, Ajay; Singh, L.K. (International Journal of Engineering and Management Research, 2025)
The financial health and development level of infrastructure in India are critical to the country's economic growth, social development, and global competitiveness. There are various infrastructure sectors, such as urban development, transport, energy, health, agriculture, education, etc., that require large-scale investments, which are often facilitated through infrastructure finance companies (IFCs) and public-private partnerships. Therefore, assessing these investments is also an important part of ensuring the smooth functioning of various stakeholders, activities, and organizations involved. This study examines the financial performance and growth trajectories of infrastructure finance companies (IFCs) operating in India. Drawing on an extensive review of existing literature, the study identifies key trends, challenges, and success factors that influence the sector's sustainability and growth. The methodology involves a qualitative and quantitative analysis of financial indicators, including profitability, liquidity, solvency, and efficiency, using secondary data sourced from annual reports, industry publications, and government databases. The findings provide insights into the operational dynamics of IFCs and offer policy recommendations to improve their performance and address sectoral challenges. This study contributes to the existing body of knowledge by integrating theoretical perspectives with empirical evidence, paving the way for more effective financial and operational strategies in the infrastructure finance domain.